Quality of Seaweed Jam (Caulerpa Racemosa) - Pebriawati, Ni Wayan Ari; Sudiarta, Ngakan Putu; Pujawan, Anak Agung Ketut Alit; Martadjaya, I Gusti Made Iwan Dusanta; Rumadana, I Made (PT FORMOSA CENDEKIA GLOBAL, 2024)
Seaweed type caulerpa racemosa is one of the green macro algae seaweeds that are often used as food for coastal communities. Caulerpa racemosa also contains antioxidants that are very beneficial for health, namely preventing triggers of degenerative diseases such as cancer, heart disease, cataracts, diabetes, liver, and antioxidants can also maintain the quality of food products. Seaweed type caulerpa racemosa is still rarely consumed by the public as a processed product. The purpose of this study was to describe the quality of seaweed-based jam (caulerpa racemosa) in terms of color, aroma, taste, texture. Data collection techniques used in this study were documentation, experimental tests and organoleptic tests. While the data analysis method used was qualitative descriptive analysis. Based on the results of the study, seaweed jam (caulerpa racemosa) which was tested on 25 panelists obtained the interpretation criteria